Sikkerhetspolitisk minnediplomati: Opprettelsen av Frigjøringsmonumentet i Kirkenes 1945-1952 - Markussen, Joakim Aalmen (Nordisk Østforum, 2021)
A few kilometers from the border with Russia, in the town of Kirkenes in the easternmost corner of Northern Norway, there stands a bronze statue of a Soviet soldier looking out over the borderland. The Soviet Liberation Monument, as the statue is called, was unveiled in 1952 by the Norwegian authorities, in gratitude for the Soviet liberation of the East Finnmark area in 1944. The statue has served as a meeting place for regular commemorative ceremonies involving the Norwegian and Soviet authorities, throughout the Cold War and up until the present. This article explores the interplay between security policy and memory politics at the onset of the Cold War by examining the seven-year long process of establishing this monument. As the Iron Curtain descended over Europe, the monument and the memories attached to it became important tools with which Norway developed a critical dialogue with its great-power neighbor. The article shows how the Norwegian Ministry of Foreign Affairs learned how to use the collective memories of the Soviet liberation to ensure Norway’s security-policy goal of low tension in its relations with the USSR.